2018
DOI: 10.1177/0363546518793657
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Pathological Gait Associated With Common Soft Tissue Running Injuries?

Abstract: 18Background: Previous research has demonstrated clear associations between specific

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
132
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(140 citation statements)
references
References 55 publications
5
132
1
2
Order By: Relevance
“…In support of this premise, a study by Braham et al reported that runners with different injuries all exhibited similar patterns among each other. However, this study only involved 72 injured runners and 36 healthy controls and a simple logistic regression model to determine which kinematic parameters could best separate the two groups. In contrast, the results of the current study used a much larger cohort and employed an unsupervised machine learning approach to reveal that certain running patterns cannot be conclusively linked to injury location and that homogeneous kinematic subgroups exist regardless of injury location.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In support of this premise, a study by Braham et al reported that runners with different injuries all exhibited similar patterns among each other. However, this study only involved 72 injured runners and 36 healthy controls and a simple logistic regression model to determine which kinematic parameters could best separate the two groups. In contrast, the results of the current study used a much larger cohort and employed an unsupervised machine learning approach to reveal that certain running patterns cannot be conclusively linked to injury location and that homogeneous kinematic subgroups exist regardless of injury location.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, associations between certain injuries and kinematic gait patterns have been detected in multiple studies . In support of this premise, a study by Braham et al reported that runners with different injuries all exhibited similar patterns among each other. However, this study only involved 72 injured runners and 36 healthy controls and a simple logistic regression model to determine which kinematic parameters could best separate the two groups.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Andrews et al discovered that genu varum knee alignment tended to generate a high knee adduction moment during the early stance phase in the gait cycle. An increased knee adduction moment during running is considered a risk factor for ITBS . As the ITB runs across the posterolateral aspects of the hip and goes down to the lateral knee, excessive frontal and transverse plane motions of the lower extremities could affect tissue strain .…”
Section: Discussionmentioning
confidence: 99%